Bioproduction of cytochalasin D by endophytic fungus Xylaria sp. DAP KRI-5 - Ahmad Fathoni, Andria Agusta (Journal of Applied Pharmaceutical Science, 2019)
Recently, endophytic fungi have attracted attention due to their ability to produce a variety of bioactive metabolites. In the course of our study on endophytic fungi associated with Albertisia papuana Becc, it has been found the endophytic fungus Xylaria sp. DAP KRI-5 produce cytochalasin D. Isolation of cytochalasin D was conducted by using an open column chromatography method. The chemical structure of cytochalasin D was deduced from 1 dimension, 2 dimension nuclear magnetic resonance, and ultra-performance liquid chromatography quadrupole time of flight mass spectrometry analyses and also compared with the published data. The bioproduction capacity of cytochalasin D by the fungus Xylaria sp. DAP KRI-5 was 0.05763 g/l.
Keywords: Isolation, characterization, bioproduction, cytochalasin D, endophytic fungus.